2006
DOI: 10.1038/sj.jp.7211612
|View full text |Cite
|
Sign up to set email alerts
|

The effects of indomethacin tocolysis on the postnatal response of the ductus arteriosus to indomethacin in extremely low birth weight infants

Abstract: Background: Antenal indomethacin reportedly decreases the responses of a symptomatic patent ductus arteriosus (sPDA) to postnatal indomethacin treatment. Whether a similar exposure affects the responses to indomethacin prophylaxis is unknown.Objective: To evaluate the clinical responsiveness of ductus arteriosus to indomethacin prophylaxis and to the treatment of sPDA in extremely low birth weight (ELBW) infants following indomethacin tocolysis.Methods: Retrospective cohort study of 58 ELBW infants whose mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This discrepancy is likely due to variations in the timing, dosage, and length of tocolytic treatments. In general, tocolytic treatments later in pregnancy ( 22 , 87 ), closer to delivery ( 90 ), with a higher dosage ( 92 ), or longer duration ( 91 , 92 ) promote PDA. Incidence aside, tocolysis has also been associated with failed pharmacological treatment and an increased need for ligation ( 22 , 88 , 89 , 91 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is likely due to variations in the timing, dosage, and length of tocolytic treatments. In general, tocolytic treatments later in pregnancy ( 22 , 87 ), closer to delivery ( 90 ), with a higher dosage ( 92 ), or longer duration ( 91 , 92 ) promote PDA. Incidence aside, tocolysis has also been associated with failed pharmacological treatment and an increased need for ligation ( 22 , 88 , 89 , 91 , 93 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, 10%-40% of patients obtain no benefits from such drugs (5). Some cohort studies or studies using regression analysis have discovered various maternal and neonatal clinical features that could be used to predict the likelihood of PDA closure with NSAIDs, such as gestational hypertension, gestational age, twin pregnancy, respiratory distress syndrome, age in days, and prenatal exposure to drugs such as magnesium sulfate and NSAIDs (5,7,(14)(15)(16)(17). Changes in urine volume or pulse pressure before and after NSAIDs treatment are not useful predictors of the responsiveness of preterm infants with PDA to a drug (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…13,14 A recent study of 58 ELBW infants whose mothers received indomethacin tocolysis and 58 ELBW control infants showed that neither the incidence of sPDA nor the responses to postnatal indomethacin have been affected by the antenatal pharmacological exposure. 15 Among the multiple factors known to decrease the response of the ductus arteriosus to postnatal indomethacin, GA and postnatal age at the time of treatment are the most relevant. [1][2]12 In humans, the ductus arteriosus constricts as early as 24-week GA, but that constriction is considered to be minimal at least until 31 weeks.…”
Section: Discussionmentioning
confidence: 99%